2012
DOI: 10.1088/1742-6596/340/1/012099
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses in biaxially fatigued austenitic stainless steel sample of cruciform geometry

Abstract: Residual stresses in biaxially fatigued austenitic stainless steel sample of cruciform geometry Research and Development Division, NECSA Limited, Pretoria, South Africa *E-mail: taran@nf.jinr.ru Abstract. A specifically designed cruciform-shaped austenitic stainless steel AISI 321 sample was subjected to ex-situ biaxial tension-compression cycling to establish ferromagnetic martensitic phase conversion under the action of plastic deformation. The time-of-flight neutron diffraction technique was employed for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the literature approaches 12,[21][22][23][24] there is no single definition to the residual stresses state in TRIP steel after martensitic transformation. Taran et al [21][22][23]25 investigated the residual stresses in AISI 321 steel using a neutron diffraction technique, after fatigue test. Taran et al 21,22 observed compressive stress for austenite and tractive stress for martensite, which decreased in magnitude with the martensite volume increases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature approaches 12,[21][22][23][24] there is no single definition to the residual stresses state in TRIP steel after martensitic transformation. Taran et al [21][22][23]25 investigated the residual stresses in AISI 321 steel using a neutron diffraction technique, after fatigue test. Taran et al 21,22 observed compressive stress for austenite and tractive stress for martensite, which decreased in magnitude with the martensite volume increases.…”
Section: Resultsmentioning
confidence: 99%
“…In the continuation of his investigation, TARAN 23 observed from total stresses calculation, the austenite phase in compression, while the martensite phase would be in balanced tractive stress of greater magnitude for smaller volumetric fraction. Investigating the distribution of radial stresses, TARAN 25 observed hydrostatic stress for austenite in its majority and compressive stress for martensite. Papula et al 12 studied the residual stresses from the (γ→α') transformation in some austenitic stainless steels after delayed cracking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation